Characteristics and prognosis of distant metastasis after primary treatment for early‐stage extranodal nasal‐type natural killer/T‐cell lymphoma from the China Lymphoma Collaborative Group database. Issue 1 (25th November 2022) - Zheng, Xuan; Qu, Bao‐Lin; Liu, Xin; Zhong, Qiu‐Zi; Qian, Li‐Ting; Yang, Yong; Hou, Xiao‐Rong; Qiao, Xue‐Ying; Wang, Hua; Zhu, Yuan; Cao, Jian‐Zhong; Wu, Jun‐Xin; et al.
Abstract: This study aimed to investigate the characteristics and prognosis of distant metastasis (DM) after primary treatment for early‐stage extranodal nasal‐type natural killer (NK)/T‐cell lymphoma (ENKTCL). A total of 1619 patients from the China Lymphoma Collaborative Group database were retrospectively reviewed. The cumulative incidence of DM was assessed using Fine and Gray's competing risk analysis. The correlation between DM sites was evaluated using phi coefficients, while DM sites were classified using hierarchical clustering. Regression analysis was used to assess the linear correlation between DM‐free survival (DMFS) and overall survival (OS). The 5‐year cumulative DM rate was 26.2%, with the highest annual hazard rate being in the first year (14.9%). The most frequent DM sites were the skin and soft tissues (SSTs, 32.4%) and distant lymph nodes (LNs, 31.3%). DM sites were categorized into four subgroups of distinct prognosis — distant LN, SST, extracutaneous site, and lymphoma‐associated hemophagocytic lymphohistiocytosis. SST or distant LN, solitary metastasis, and late‐onset DM demonstrated a relatively favorable prognosis. Contemporary chemotherapy significantly decreased DM rates and improved DMFS. Decreased DM rates were further associated with increased OS probabilities. Our findings improve the understanding of the variable clinical behaviors of early‐stage ENKTCL based on four distinct DM sites and thus provide guidance for future therapeutic decisions, metastatic surveillance, and translational trial design.